Routes to reform: civil-military relations and democracy in the third wave - Kühn, David; Croissant, Aurel (Oxford University Press, 2023)
This volume examines the conditions under which new democracies succeed or fail in establishing firm and lasting civilian control of the military. It introduces a multi-dimensional conceptual framework to evaluate the degree of civilian control in new democracies, and tests a new theory on a large dataset from 66 countries.
Keywords: Zivil-militärische Zusammenarbeit; Demokratisierung; Demokratie